Effect of Location of Infill Walls on the Dynamic Performance of the RC Framed Building - R., Shilpa; Sonamma (AMC Indian Journal of Civil Engineering, 2024)
Infill frame structures are utilized to provide lateral stability in areas with high seismic activity, particularly where masonry remains a practical choice due to cost and tradition. They also help reduce bending moments in the frame, thereby lowering the risk of collapse. Seismic analysis has been conducted using the "Equivalent Static Analysis Method" on various reinforced concrete frame models, including a bare frame without infill, infilled frames at the interior only, exterior only, both interior and exterior, and infill between the interior and exterior. All models were modeled and analyzed using ETABS software. Infilled frames are preferred over open-storey frames in seismic regions because the presence of infill walls significantly influences the seismic behavior of the structure, enhancing its strength and stiffness. In contrast, open-storey frame structures tend to experience much greater storey drift than upper levels, increasing the risk of collapse during a strong earthquake.